2014
DOI: 10.3390/d6020323
|View full text |Cite
|
Sign up to set email alerts
|

Planarian (Platyhelminthes, Tricladida) Diversity and Molecular Markers: A New View of an Old Group

Abstract: Planarians are a group of free-living platyhelminths (triclads) best-known largely due to long-standing regeneration and pattern formation research. However, the group's diversity and evolutionary history has been mostly overlooked. A few taxonomists have focused on certain groups, resulting in the description of many species and the establishment of higher-level groups within the Tricladida. However, the scarcity of morphological features precludes inference of phylogenetic relationships among these taxa. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 48 publications
3
12
0
2
Order By: Relevance
“…The separate origins of asexual fissioning contradict the traditional assumption that asexual fissioning is a basal macrostomorphan reproductive strategy shared with the Catenulida (Rieger, 1986(Rieger, , 2001, and casts additional doubts on the proposed plesiomorphy of asexual reproduction in Platyhelminthes, and even in early divergent Bilateria (Ehlers, 1985;Rieger, 1986). Indeed, Jondelius et al (2011) found asexual fissioning to be a derived feature in the Acoela, and also within the Tricladida there seem to be multiple origins of asexual fissioning (Riutort et al, 2012;Álvarez-Presas and Riutort, 2014). Interestingly, there seems to be a clear link between the presence of asexual fissioning and the capability of regeneration (Egger et al, 2007), suggesting that the presence of a totipotent neoblast stem cell system may play a crucial role in the evolution of asexual fissioning (Martín-Durán and Egger, 2012).…”
Section: Evolution Of Asexual Fissioningmentioning
confidence: 80%
“…The separate origins of asexual fissioning contradict the traditional assumption that asexual fissioning is a basal macrostomorphan reproductive strategy shared with the Catenulida (Rieger, 1986(Rieger, , 2001, and casts additional doubts on the proposed plesiomorphy of asexual reproduction in Platyhelminthes, and even in early divergent Bilateria (Ehlers, 1985;Rieger, 1986). Indeed, Jondelius et al (2011) found asexual fissioning to be a derived feature in the Acoela, and also within the Tricladida there seem to be multiple origins of asexual fissioning (Riutort et al, 2012;Álvarez-Presas and Riutort, 2014). Interestingly, there seems to be a clear link between the presence of asexual fissioning and the capability of regeneration (Egger et al, 2007), suggesting that the presence of a totipotent neoblast stem cell system may play a crucial role in the evolution of asexual fissioning (Martín-Durán and Egger, 2012).…”
Section: Evolution Of Asexual Fissioningmentioning
confidence: 80%
“…Although stygobiont freshwater triclads have received a good deal of attention (cf. Gourbault, , and references therein), many more studies have been published on planarians from epigean freshwaters, which have been extensively studied from all over the world (Sluys, Kawakatsu & Winsor, ; Sluys et al ., ; Lazaro et al ., ; Harrath et al ., ; Harrath et al ., ; Stocchino, Sluys & Manconi, ; Sluys, Kawakatsu & Timoshkin, ; Álvarez‐Presas & Riutort, ).…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, EF behaves the same way as the mitochondrial genes at this level, and it lacks sufficient resolution. However, concatenated genes produced better resolved phylogenies than the ones obtained from the individual genes alone, as stated in Álvarez‐Presas and Riutort (2014). This situation, where genes with different resolutions provide a more robust tree when concatenated, may be explained by the influence that each gene has at different levels of a tree (Baldauf et al., 2000) or simply by the fact that longer sequences would result in smaller variances (Gadagkar et al., 2005).…”
Section: Discussionmentioning
confidence: 62%
“…These sequences belong to representatives of most of the genera of the Neotropical Geoplaninae, plus representatives of the three other land planarian subfamilies. Representatives of the freshwater family Dugesiidae were used as outgroup (Álvarez‐Presas et al., 2008; Álvarez‐Presas & Riutort, 2014) (Table ). These data include the only two Chilean, undescribed species of land planarians that have DNA sequences available in the GenBank database, (i.e.…”
Section: Methodsmentioning
confidence: 99%